Hedging by Raisa on Eric Nam’s Podcast ‘Daebak Show’ - Salca Pragita; Dewi Nuryanti (Anaphora : Journal of Language, Literary, and Cultural Studies, 2022)
This research aims to investigate the hedging devices used by Raisa that occurred on Eric Nam’s Podcast Daebak Show Ep.138. It also aims to find out the type of hedging, the meaning of the hedging, and the purpose of using the hedging device by Raisa as a guest star on Eric Nam’s Podcast Daebak Show Ep.138. It is qualitative descriptive research. The object is data from Raisa’s utterances on Eric Nam’s podcast containing lexical hedging in words, phrases, or clauses. In the analysis, the theory used is the theory of taxonomy hedging by Salager-Meyer. The result of this research shows three results. The first result is the type of hedging used by Raisa that consists of five types: 1) modal verbs; 2) adjectival, adverbial, nominal modal verbs; 3) approximators of degree, quantity, frequency, and time; 4) introductory phrases; and 5) “if” clause. The next result is the purpose of hedging by Raisa, who tends to show politeness, make the sentence vaguer and less certain, tone down the force of the statement, and avoid the threatening statement by her addressee. The last result of this research shows how hedging by Raisa means saving her image and her addressee’s image.